2017
DOI: 10.1186/s13690-017-0230-8
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary time among primary school children in south-west Germany: amounts and correlates

Abstract: BackgroundSedentary behaviour in children is related to different health consequences such as overweight and cardio-metabolic diseases that can track into adulthood. Previous studies have shown that children spend hours being sedentary, but no data of sedentary time (ST) among German children has been available, yet. Therefore, this study investigated objectively measured amounts and correlates of ST in a sample of German primary school children.MethodsChildren’s physical activity (PA) was objectively assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 55 publications
(68 reference statements)
1
5
1
Order By: Relevance
“…Consistent with other studies [ 20 , 22 , 23 ], we found that boys were more active than girls, which might be explained by greater participation in active transportation [ 31 ], organized sports activities [ 22 ], and a higher level of MVPA in physical education lessons [ 41 ]. The finding that boys were more sedentary than girls in this study was inconsistent with other studies [ 23 , 31 , 42 ] and might be explained by measures that lack questions specific to activities that girls’ enjoy to potentially reduce their actual SED time [ 43 ]. Consequently, extensive measures reflecting girls’ daily SED are needed in future studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with other studies [ 20 , 22 , 23 ], we found that boys were more active than girls, which might be explained by greater participation in active transportation [ 31 ], organized sports activities [ 22 ], and a higher level of MVPA in physical education lessons [ 41 ]. The finding that boys were more sedentary than girls in this study was inconsistent with other studies [ 23 , 31 , 42 ] and might be explained by measures that lack questions specific to activities that girls’ enjoy to potentially reduce their actual SED time [ 43 ]. Consequently, extensive measures reflecting girls’ daily SED are needed in future studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Evidently, schoolrelated sitting is dominant (Demetriou et al 2019), but also leisure time accounts for additional ST, with the result that 9.4 h in this sample and 10.6 h in Huber and Köppels' (2017) sample of 4-to 20-year-olds were spent in a sedentary position. Referring to Hoffmann et al (2017), sample primary students are less sedentary, with 3.7 h ST on schooldays than secondary female students in UK, with 6.2 h ST (Bailey et al 2012). Self-reported data of numerous studies hold media consumption (e.g., screen time) to be accountable for high SB Bucksch and Dreger 2014;Konstabel et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a variety of researches seeks to understand the factors that influence individual behaviors related to PA or sedentary behavior [ 12 , 20 , 21 ]. However, only a few studies seek to understand the primary factors that can influence adolescents’ movement behavior combinations.…”
Section: Introductionmentioning
confidence: 99%